ILUSTRASI 3D HARDWARE PADA KOMPUTER UNTUK MATAKULIAH PRAKTIKUM PENGANTAR TERKNOLOGI INFORMASI - Gus Oka Ciptahadi (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2020)
Abstract: Practicum Introduction to Information Technology is a general course that is always present at every IT campus in Indonesia. To give an introduction to hard ware to students, each lecturer always requires a long time, because they have to open (CPU) the Central Processing Unit and release other components to be explained by students. Inefficient time in opening and releasing computer hardware components when the course is taking place is the main problem that will be solved by researchers in this study. Plus the computer components that will be explained are quite small, making students unable to see it clearly when in the teaching and learning process. The offered solution, utilizing a technology based on 3D animation. Where this 3D animation technology will provide a more realistic appearance. As in the study entitled SINDO JOURNALIST 3D FILM ANIMATION in the journal Art Design and Culture volume 2. No. 1 March 2017, which researchers have reviewed, also explained that the use of 3D design technology can produce vivid and real visuals that are close to their original form [1]. The method in developing 3D animation in this study uses the Reseach and Development (R&D) Method. Conclusions from this study, researchers have succeeded in making a 3D animation-based information media about the introduction of computer hardware for the Introduction to Information Technology Practicum, with the process of animation results that have been tested using blackbox test.            Keywords: animation; hardware; research and development  Abstrak: Mata kuliah praktikum Pengantar Teknologi Informasi adalah matakuliah umum yang selalu terdapat pada setiap kampus IT di Indonesia. Untuk memberikan pengenalan hardware kepada peserta didik, setiap dosen selalu membutuhkan waktu yang cukup lama, dikarenakan harus membuka (CPU) Central Processing Unit dan melepaskan komponen lainnya agar dapat dijelaskan oleh peserta didik. Tidak efisiennya waktu  dalam membuka dan melepaskan komponen hardware komputer ketika matakuliah berlangsung menjadi permasalahan utama yang akan diselesaikan peneliti dalam penelitian kali ini. Ditambah lagi komponen komputer yang akan dijelaskan cukup kecil, membuat peserta didik tidak dapat melihatnya dengan jelas ketika dalam proses belajar mengajar. Solusi yang ditawarkan, memanfaatkan sebuah teknologi berbasis 3D animasi. Dimana teknologi 3D animasi ini akan memberikan tampilan yang lebih realistis. Metode didalam pengembangan animasi 3D pada penelitian ini menggunakan Metode Reseach and Development (R&D). Simpulan dari penelitian ini, peneliti sudah berhasil membuat sebuah media informasi berbasis animasi 3D tentang pengenalan hardware komputer untuk matakuliah Praktikum Pengantar Teknologi Informasi, dengan proses hasil animasi yang sudah diuji dengan menggunakan blackbox testing. Kata kunci: animasi; hardware; reseach and development.